[OP.8C.04] THE FLOW DETECTION ROLE OF THE VASCULAR EPITHELIAL SODIUM CHANNEL (ENAC) IN AN EXPERIMENTAL MODEL OF HYPERTENSION: THE NOVEL TARGET FOR SPIRONOLACTONE THERAPY?. (September 2016) - Ashley, Z.; Leader, C.; Sammut, I.; McDonald, F.; Walker, R.; Fronius, M.
Abstract : Objective: Hypertension (HTN) impairs the regulation of blood flow leading to cardiovascular morbidity and mortality. A "new player" in blood-flow regulation is the endothelium Epithelial Sodium Channel (vascular ENaC). We hypothesise that dysfunction in HTN is due to changes in vascular ENaC activity. Aldosterone regulates renal ENaC and has a pivotal role in HTN and recently it has been suggested that aldosterone antagonism (spironolactone therapy) is beneficial beyond that predicted by the reduction in blood pressure. We propose that these additional effects are due to re-establishment of normal vascular function through modulation of vascular ENaC activity. Design and method: An experimental model of HTN, compared to normotensive (NTN) controls, with/without spironolactone therapy (n = 3–5) was used. HTN was induced in adult male transgenic rats (TG strain: Cyp1a1-Ren2), via diet-driven (0.167% w/w indol-3-carbinol) activation of renin-angiotensin-aldosterone system. Spironolactone treatment was administered daily (orally, 8.8 mg/kg/day) starting 7 weeks following initiation of HTN. Flow-mediated changes in the internal diameter (% change from no-flow) of isolated 3rd order mesenteric arteries, in the presence/absence of 10 μM amiloride were measured to determine the role of ENaC. Flow was induced through the vessels, whilst mean intraluminal pressure was maintained at 60 mmHg. Results: Isolated NTN arteries demonstrated flow mediated-constriction (−9.9 ± 3.6%) under basal conditions which was reduced (−6.3 ± 3.1%) by amiloride. The basal response was absent in HTN (0.8 ± 1.0%) vessels, and unaffected by amiloride (0 ± 1.5%). Spironolactone treatment of NTN rats resulted in a slight augmentation (−11.8 ± 1.9 %) of flow-mediated constriction which was unaffected by amiloride (−11.6 ± 1.7%). Spironolactone treatment did not improve the lack of flow-mediated response of HTN vessels (0.5 ± 0.7%), and was unaffected by amiloride (−0.4 ± 1.3%). Conclusions: Vascular ENaC activity augments flow-mediated constriction of mesenteric arteries. The attenuation of flow-mediated responsiveness in experimental RAAS-driven HTN is linked, in part, to a reduction in vascular ENaC activity. Spironolactone augments flow-mediated responsiveness of NTN vessels, although this may not be through increased ENaC activity. Initiation of spironolactone treatment at a late stage of HTN doesn't appear to modulate ENaC function or re-establish normal vascular function.